Gender dysphoria in an adolescent diagnosed with Klinefelter syndrome over a follow-up period - Tunas, Sabide Duygu; Dinc, Gulser; Goker, Zeynep; Uneri, Ozden Sukran (The European Research Journal, 2018)
Although genetic factors have been thought to be main cause for gender dysphoria, its etiology is still not clearly understood. Klinefelter syndrome is the most seen sex chromosomal disorder. In the literature, there are fewer case reports in connection with Klinefelter syndrome and gender dysphoria. Herein, we report a 16-year-old adolescent patient displaying gender dysphoria features, who has revealed Klinefelter syndrome after genetic examination, and has been treated with testosterone hormone, and his gender dysphoria symptoms have disappeared. In our case, chromosomal anomaly and lower levels of androgen could play a role in the etiopathogenesis of gender dysphori. Bringing Klinefelter syndrome disorder to mind in gender dysphoria cases, even it is a rare disorder, could positively affect the course of the treatment as was in our case. The relation between psychiatric symptoms, which can be seen in gender dysphoria, and testosterone does not known exactly. Further studies, which are randomized-controlled ones, can help to better understand the subject.